2009
DOI: 10.1590/s0004-282x2009000300014
|View full text |Cite
|
Sign up to set email alerts
|

Performance of 119 Brazilian children on Stroop paradigm: Victoria version

Abstract: -Background: The Stroop paradigm evaluates susceptibility to interference and is sensitive to dysfunction in frontal lobes. Performance in the Stroop changes along the development. Despite its usefulness in research and clinical settings, there are few studies with Brazilian samples. Objective: This study investigates the performance and age effect on Stroop paradigm of Brazilian children. Method: A sample of 119 children, aged from 7 to 10 years, was submitted to the Victoria version of Stroop. Results: The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
1
13
0
4
Order By: Relevance
“…Adult studies suggest that greater interference is sometimes observed with vocal compared to manual responses (White, 1969; Redding and Gerjets, 1977; MacLeod, 1991). Although the response times we observed were much faster (i.e., under 1 s, Figure 2) than those requiring verbal response (Comalli et al, 1962; Schiller, 1966; Berninger et al, 1991; Armengol, 2002; Leon-Carrion et al, 2004; Pritchard and Neumann, 2004; Peru et al, 2006; Charchat-Fichman and Oliveira, 2009; Polderman et al, 2009), relations with age were strong; we showed that age shared approximately 33% of the variance with all conditions (Table 3). Inter-correlations with conditions were stronger, showing greater common variance ranging from 53 to 74%.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Adult studies suggest that greater interference is sometimes observed with vocal compared to manual responses (White, 1969; Redding and Gerjets, 1977; MacLeod, 1991). Although the response times we observed were much faster (i.e., under 1 s, Figure 2) than those requiring verbal response (Comalli et al, 1962; Schiller, 1966; Berninger et al, 1991; Armengol, 2002; Leon-Carrion et al, 2004; Pritchard and Neumann, 2004; Peru et al, 2006; Charchat-Fichman and Oliveira, 2009; Polderman et al, 2009), relations with age were strong; we showed that age shared approximately 33% of the variance with all conditions (Table 3). Inter-correlations with conditions were stronger, showing greater common variance ranging from 53 to 74%.…”
Section: Discussionmentioning
confidence: 60%
“…Specifically, age accounted for slightly more variance in the Incongruent factor and for the least amount for variance for the Word-congruent. Previous research on the Stroop documented that children became progressively faster as they responded verbally to stimuli (Comalli et al, 1962; Schiller, 1966; Berninger et al, 1991; Armengol, 2002; Leon-Carrion et al, 2004; Pritchard and Neumann, 2004; Peru et al, 2006; Charchat-Fichman and Oliveira, 2009; Polderman et al, 2009), and this was what we also found with speeded manual responses (Figure 2; Table 3). Adult studies suggest that greater interference is sometimes observed with vocal compared to manual responses (White, 1969; Redding and Gerjets, 1977; MacLeod, 1991).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…La tarea experimental Stroop Victoria (Mueller & Piper, 2014) es una tarea de control inhibitorio basada en el paradigma Stroop clásico (Troyer, Leach, & Strauss, 2006), la cual está desarrollada en una versión informatizada, en donde se utiliza un computador para poder realizarlo. Esta tarea consta de 3 fases (cada una de 26 estímulos) (Charchat-Fichman & Martins, 2009). En la primera fase el participante debe presionar los botones adecuados que indiquen el color (azul, rojo, amarillo y verde) de los círculos presentados en el monitor (ver Figura 1).…”
Section: Instrumentos Y Técnicas De Mediciónunclassified